PENGARUH KOMPENSASI, MOTIVASI, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN MEBEL ROTTAN JATI JAYA - Pratiwi, Pipit Puji; Bagus Honor Satrya, I Gusti (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.06.TAHUN.2023, 2023)
Employee performance is influenced by various factors including compensation, motivation, and work environment. All three have an important role in improving employee performance. This study aims to determine the effect of compensation, motivation, and work environment on employee performance at the Rottan Jati Jaya Furniture Company. The type of research used is quantitative. The population is Furniture Rottan Jati Jaya employees and the sample is taken using a saturated sampling technique with a total of 42 respondents. The data collection includes questionnaires and interviews. The analytical methods used are validity test, reliability test, classical assumption test, multiple linear analysis and hypothesis testing and the coefficient of determination. The results showed that compensation has a positive and significant effect on employee performance, motivation has a positive and insignificant effect on employee performance, the work environment has a positive and insignificant effect on employee performance. This indicates that the higher the compensation, the higher the employee's performance, if the motivation and work environment are higher, the higher the effect on employee performance but not significant.